Penyuluhan Tabungan SimPel Untuk Membangun Kesadaran Menabung Pada Siswa SMK PGRI Klungkung - Cantika, Cantika Nevita Sari; Wirsa, I Nengah (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The service took the form of socialization and counseling activities about "Bank BPD Bali Goes To School" for Klungkung PGRI Vocational High School students. Considering the low culture of saving among students, especially saving at the bank. This activity aims to provide knowledge and understanding of how to save using SimPel Savings and how to save properly with pocket money given by parents. The activity method uses stages including: 1). Convey or inform the school that there will be socialization and counseling programs; 2). Collection of information about problems that exist in schools; 3). We prepare material to be disseminated; 4). The Bank also prepares banners and door prizes; 5). Implementation of socialization regarding saving. The material presented regarding Simpel is the definition of SimPel savings, the benefits of Simpel Savings, and how to save using Simpel Savings and plus how much the initial deposit is to make Simple Savings. The results of this activity received a good response from students and teachers. Begin to understand what Simple Savings is, how to save properly, and the benefits of saving for the long term. Keywords: Bank BPD Bali, Simple Savings, Benefits of Saving